PENGARUH VARIASI KONSENTRASI PREKURSOR TERHADAP KARAKTERISASI NANOPARTIKEL ZINC OXIDE DENGAN METODE SOL-GEL - Rahman, Purnama Auliya; Junus, Salahuddin; Hardiatama, Intan; Nashrullah, M Dimyati; Nurdiansyah, Haidzar (Jurusan Teknik Mesin, 2024)
Nanomaterial research, especially in the field of experimentation, cannot be separated from characterization or measurement activities, with characterization we can be sure that the synthesized material meets the nanostructure criteria, one of which is nanometer-sized. In this study we will characterize ZnO nanomaterials from the sol-gel method. Sol-gel is a chemical method that changes the state of the sol (liquid) into a gel state which is then after treatment and the transition to solid oxide material. Zinc Oxide nanoparticles are made with variations in the precursor of Zinc Acetate Dyhidrate 0.3 M and 0.1 M produce crystalline nanomaterial sizes of 157-123 nm. The crystal lattice parameters obtained are a = 3.2714 Å and c = 5.2121 Å and structural characterization revealed a single phase of ZnO with hexagonal wurtzite structure. For the average particle size of Zinc Oxide nanoparticle produced is 86,64-12,60 nm and the morphological form of ZnO nanoparticles produced is spherical and particles agglomerate. The final results show that the increase in the variation of the Zinc Acetate Dyhidrate precursor will increase both the crystal size and the size of the particles produced.